Relation of skinfold thickness and visceral fat with the endothelial function in Mexican postmenopausal women - Carranza-Lira, Sebastián; Fino Muro, Ana Mirna; Rosales Ortiz, Sergio (Menopause Review/Przegląd Menopauzalny, 2015)
Objective: To determine the relationship between skinfolds and visceral fat with vascular reactivity according to body weight, fat distribution and time since menopause in Mexican postmenopausal women. Material and methods: In postmenopausal women, tricipital, suprailiac and subscapular skinfolds as well as blood pressure were measured, and body mass index (BMI) and waist-hip ratio (WHR) were calculated. Brachial artery Doppler ultrasound at baseline and after the hyperemic stimulus was done and Doppler parameters were assessed. For statistical analysis, Pearson and Spearman correlation analysis, as well as Student t were used. Results: Sixty-six postmenopausal women were studied; age was 54.5 ± 7.4 years. Skinfold thickness was related with subcutaneous and visceral fat. In all groups, the arterial diameter increased after the hyperemic stimulus among 6.5% and 9% of women. The pulsatility index decreased in the whole group and in those with BMI ≤ 27, WHR ≤ 0.85 and time since menopause ≤ 10 years. Negative correlations were observed between the percentage of change in arterial dilatation and the subscapular skinfold and subcutaneous fat in the whole group and in the subgroups with BMI > 27 and WHR > 0.85. Conclusions: Skinfolds are indirectly related with visceral fat, and skinfold thickness permit to conclude about impact in endothelial environment.